Book Reviews - Dubner, Steven; Hoover, James L.; Weinberg, Joanna Kudisch (Columbia Journal of Environmental Law, 2020)
Mercury Contamination: A Human Tragedy. By Patricia A. D'Itri and Frank M. D'Itri. New York: John Wiley & Sons, Inc. 1977. Pp. xxii, 311. $17.95. NATURE, BUREAUCRACY AND THE RULES OF PROPERTY: REGULATING THE RENEWING ENVIRONMENT. By Earl Finbar Mur- phy. Amsterdam: North-Holland Publishing Co. 1977. Pp. xii, 335. $44.50. PRINCIPLES FOR LOCAL ENVIRONMENTAL MANAGEMENT. By Peter G. Rowe et. al., Cambridge, Massachusetts: Ballinger Publishing Co. 1978. Pp. xviii, 272. $17.50.